Anaplasia in Wilms tumor: A critical review - Gordan M. Vujanić (14778694) (2024)
Anaplasia in Wilms tumor is recognized as the most important prognostically unfavorable histological feature. It is subtyped as focal anaplastic Wilms tumor (FAWT) and diffuse anaplastic Wilms tumor (DAWT). Outcomes of patients with DAWT remain poor in patients with stage III and IV tumors. Important issues relevant to anaplasia in Wilms tumor, including prevalence, treatment, outcomes, biomarkers, anaplasia, and chemotherapy, and the concept of tumor aggressiveness, are reviewed and discussed here. We also consider the differences in clinical approaches to anaplasia in Wilms tumor between the two major renal tumor clinical research groups: the International Society of Paediatric Oncology (SIOP) Renal Tumour Study Group and the Children's Oncology Group (COG) Renal Tumor Group. We emphasize the importance and implications of recognizing FAWT and DAWT as separate clinico‐pathological entities. Other Information Published in: Pediatric Blood & Cancer License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/pbc.31000